PATHOLOGY IN PUBLIC SERVICE OR LOW DUE TO LACK OF KNOWLEDGE AND SKILLS OF EXECUTIVE OFFICERS OF THE VARIOUS OPERATIONAL ACTIVITIES - Hamirul, Hamirul (Prosiding International conference on Information Technology and Business (ICITB), 2016)
Â A primary issue in this study is to identify the type of pathology experienced Cimahi city land office, and what strategies can be applied in order to minimize pathologies arising from lack of or lack of knowledge and skills of the officers of various operational activities.The results of the research office of the land Cimahi in serving the public is still suffering from pathologies that are caused due to the lack or low level of knowledge and skills of the officers of various operational activities, such as: do not be able to outline the wisdom of leadership, lack of carefully situations, smugness, acting without thinking, confused, baksheesh, a lower quality of work, superficiality, inaccuracies action, incompetence, hesitant attitude, work is not productive, untidiness, stagnation.Some of the strategies that can be done in minimizing the pathology of this type that the transparency of the time and cost in managing certificates by strengthening the administration, education and trainning.KEY WORDS:Pathology Bureaucracy,Â  service quality.